A quantitative assessment of the hydrogen storage capacity of the UK continental shelf. (16th February 2021) - Scafidi, Jonathan; Wilkinson, Mark; Gilfillan, Stuart M.V.; Heinemann, Niklas; Haszeldine, R. Stuart
Abstract: Increased penetration of renewable energy sources and decarbonisation of the UK's gas supply will require large-scale energy storage. Using hydrogen as an energy storage vector, we estimate that 150 TWh of seasonal storage is required to replace seasonal variations in natural gas production. Large-scale storage is best suited to porous rock reservoirs. We present a method to quantify the hydrogen storage capacity of gas fields and saline aquifers using data previously used to assess CO2 storage potential. We calculate a P50 value of 6900 TWh of working gas capacity in gas fields and 2200 TWh in saline aquifers on the UK continental shelf, assuming a cushion gas requirement of 50%. Sensitivity analysis reveals low temperature storage sites with sealing rocks that can withstand high pressures are ideal sites. Gas fields in the Southern North Sea could utilise existing infrastructure and large offshore wind developments to develop large-scale offshore hydrogen production. Graphical abstract: Image 1 Highlights: UK requires 150 TWh of seasonal hydrogen storage capacity to decarbonise gas. First quantification of hydrogen storage capacity in gas fields. 6900 TWh hydrogen working gas capacity in UK offshore gas fields. Low temperature/high pressure capacity storage sites are best. Offshore gas fields and wind could develop offshore hydrogen production.